AKUNTANSI LINGKUNGAN DAN NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Chairina, Septi Wulandari; SE MSi, Sulhendri; Suharti, Emi (Universitas Kristen Krida Wacana, 2024)
The trend of sustainability is increasingly drawing attention from the public, investors, and governments. There is an interesting debate regarding the impact of implementing green accounting on firm value. Some argue that green accounting can enhance firm value by attracting investors who are concerned about environmental issues. On the other hand, while environmental costs may reduce profitability in the short term, their impact on firm value could vary. This study aims to estimate and analyze the relationship between Environmental Accounting and Firm Value with Financial Performance as an Intervening Variable in companies that have achieved PROPER ratings in the gold and green categories. The analysis of direct effects was conducted using eviews software, while indirect effects were analyzed using the sobel test. The results of the study show that, directly, environmental costs, environmental performance, and financial performance have a significant partial effect on firm value. Conversely, environmental disclosure does not significantly affect firm value. Regarding the indirect effects, it was found that environmental costs and environmental performance are successfully mediated by financial performance in their impact on firm value, while environmental disclosure is not successfully mediated by financial performance. This research indicates that companies’ efforts to improve environmental performance and allocate environmental costs effectively can enhance firm value, particularly when supported by strong financial performance. Therefore, companies should focus on tangible efforts in environmental management while maintaining financial performance stability to strengthen their value in the eyes of stakeholders, including investors and other relevant parties. Keywords: Environmental Performance, Environmental Disclosure, Environmental Costs, Financial Performance, Company Value